Insects of Western North America 8. The checkered beetle genus Trichodes Herbst (Coleoptera: Cleridae): a pictorial key to North American taxa with notes on Colorado species - West, Daniel R., author; C.P. Gillette Museum of Arthropod Diversity, publisher (Colorado State University. Libraries, 2014)
The Trichodes is a genus of checkered beetles (Cleridae: Clerinae) consisting predominately of predators of hymenopteran larvae and orthopteran egg pods (Foster, 1976). Adult Trichodes are floral visitors, feeding on pollen, mating on flowers, and ovipositing on flowers visited by Apoidea or oviposit directly into nests of ground dwelling bees. Three species inhabiting montane and plateau counties of western Colorado were recorded: T. nutalli, T. ornatus, T. simulator. The genus appears to be absent from the Great Plains Steppe Province of the eastern Colorado. A pictorial key for all North American species of Trichodes and recognized subspecies of T. ornatus is presented. Notes on the biology of three Colorado species are given. Available county records are also noted.
The checkered beetle genus Trichodes Herbst (Coleoptera: Cleridae): a pictorial key to North American taxa with notes on Colorado species
February 5, 2014.
Keywords: checkered beetles; Trichodes Herbst; Coleoptera; Cleridae